Memorias de poligamia una perspectiva antropológica - Alshboul, Ayman M. Q. (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The goal of this investigation is to analyze the polygamy as made fact, on smaller scale, by some men of the Jordanian society; also to examine its objectives, measures and functions by which were made the decision from the second marriage. The polygamy is not rejected and it is not accepted either, but that must be justified, be reasoned and to have the approval of the first wife first and her children, if it has them, secondly and of the relatives more close friends finally.